70-gene signature as an aid for treatment decisions in early breast cancer: updated results of the phase 3 randomised MINDACT trial with an exploratory analysis by age. Issue 4 (April 2021) - Piccart, Martine; van 't Veer, Laura J; Poncet, Coralie; Lopes Cardozo, Josephine M N; Delaloge, Suzette; Pierga, Jean-Yves; Vuylsteke, Peter; Brain, Etienne; Vrijaldenhoven, Suzan; Neijenhuis, Peter A; Causeret, Sylvian; Smilde, Tineke J; et al.
Summary: Background: The MINDACT trial showed excellent 5-year distant metastasis-free survival of 94·7% (95% CI 92·5–96·2) in patients with breast cancer of high clinical and low genomic risk who did not receive chemotherapy. We present long-term follow-up results together with an exploratory analysis by age. Methods: MINDACT was a multicentre, randomised, phase 3 trial done in 112 academic and community hospitals in nine European countries. Patients aged 18–70 years, with histologically confirmed primary invasive breast cancer (stage T1, T2, or operable T3) with up to three positive lymph nodes, no distant metastases, and a WHO performance status of 0–1 were enrolled and their genomic risk (using the MammaPrint 70-gene signature) and clinical risk (using a modified version of Adjuvant! Online) were determined. Patients with low clinical and low genomic risk results did not receive chemotherapy, and patients with high clinical and high genomic risk did receive chemotherapy (mostly anthracycline-based or taxane-based, or a combination thereof). Patients with discordant risk results (ie, patients with high clinical risk but low genomic risk, and those with low clinical risk but high genomic risk) were randomly assigned (1:1) to receive chemotherapy or not based on either the clinical risk or the genomic risk. Randomisation was done centrally and used a minimisation technique that was stratified by institution, risk group, and clinical–pathological characteristics. Treatment allocation was not masked. The primary endpoint was to test whether the distant metastasis-free survival rate at 5 years in patients with high clinical risk and low genomic risk not receiving chemotherapy had a lower boundary of the 95% CI above the predefined non-inferiority boundary of 92%. In the primary test population of patients with high clinical risk and low genomic risk who adhered to the treatment allocation of no chemotherapy and had no change in risk post-enrolment. Here, we present updated follow-up as well as an exploratory analysis of a potential age effect (≤50 years vs >50 years) and an analysis by nodal status for patients with hormone receptor-positive and HER2-negative disease. These analyses were done in the intention-to-treat population. This study is registered with ClinicalTrials.gov, NCT00433589, and the European Clinical Trials database, EudraCT2005–002625–31. Recruitment is complete and further long-term follow-up is ongoing. Findings: Between Feb 8, 2007, and July 11, 2011, 6693 patients were enrolled. On Feb 26, 2020, median follow-up was 8·7 years (IQR 7·8–9·7). The updated 5-year distant metastasis-free survival rate for patients with high clinical risk and low genomic risk receiving no chemotherapy (primary test population, n=644) was 95·1% (95% CI 93·1–96·6), which is above the predefined non-inferiority boundary of 92%, supporting the previous analysis and proving MINDACT as a positive de-escalation trial. Patients with high clinical risk and low genomic risk were randomly assigned to receive chemotherapy (n=749) or not (n=748); this was the intention-to-treat population. The 8-year estimates for distant metastasis-free survival in the intention-to-treat population were 92·0% (95% CI 89·6–93·8) for chemotherapy versus 89·4% (86·8–91·5) for no chemotherapy (hazard ratio 0·66; 95% CI 0·48–0·92). An exploratory analysis confined to the subset of patients with hormone receptor-positive, HER2-negative disease (1358 [90.7%] of 1497 randomly assigned patients, of whom 676 received chemotherapy and 682 did not) shows different effects of chemotherapy administration on 8-year distant metastasis-free survival according to age: 93·6% (95% CI 89·3–96·3) with chemotherapy versus 88·6% (83·5–92·3) without chemotherapy in 464 women aged 50 years or younger (absolute difference 5·0 percentage points [SE 2·8, 95% CI −0·5 to 10·4]) and 90·2% (86·8–92·7) versus 90·0% (86·6–92·6) in 894 women older than 50 years (absolute difference 0·2 percentage points [2·1, −4·0 to 4·4]). The 8-year distant metastasis-free survival in the exploratory analysis by nodal status in these patients was 91·7% (95% CI 88·1–94·3) with chemotherapy and 89·2% (85·2–92·2) without chemotherapy in 699 node-negative patients (absolute difference 2·5 percentage points [SE 2·3, 95% CI −2·1 to 7·2]) and 91·2% (87·2–94·0) versus 89·9% (85·8–92·8) for 658 patients with one to three positive nodes (absolute difference 1·3 percentage points [2·4, −3·5 to 6·1]). Interpretation: With a more mature follow-up approaching 9 years, the 70-gene signature shows an intact ability of identifying among women with high clinical risk, a subgroup, namely patients with a low genomic risk, with an excellent distant metastasis-free survival when treated with endocrine therapy alone. For these women the magnitude of the benefit from adding chemotherapy to endocrine therapy remains small (2·6 percentage points) and is not enhanced by nodal positivity. However, in an underpowered exploratory analysis this benefit appears to be age-dependent, as it is only seen in women younger than 50 years where it reaches a clinically relevant threshold of 5 percentage points. Although, possibly due to chemotherapy-induced ovarian function suppression, it should be part of informed, shared decision making. Further study is needed in younger women, who might need reinforced endocrine therapy to forego chemotherapy. Funding: European Commission Sixth Framework Programme.